Role of YAP/TAZ in Cell Lineage Fate Determination and Related Signaling Pathways - Heng, Boon C.; Zhang, Xuehui; Aubel, Dominique; Bai, Yunyang; Li, Xiaochan; Wei, Yan; Fussenegger, Martin; Deng, Xuliang (Frontiers in Cell and Developmental Biology, 2020)
The penultimate effectors of the Hippo signaling pathways YAP and TAZ, are transcriptional co-activator proteins that play key roles in many diverse biological processes, ranging from cell proliferation, tumorigenesis, mechanosensing and cell lineage fate determination, to wound healing and regeneration. In this review, we discuss the regulatory mechanisms by which YAP/TAZ control stem/progenitor cell differentiation into the various major lineages that are of interest to tissue engineering and regenerative medicine applications. Of particular interest is the key role of YAP/TAZ in maintaining the delicate balance between quiescence, self-renewal, proliferation and differentiation of endogenous adult stem cells within various tissues/organs during early development, normal homeostasis and regeneration/healing. Finally, we will consider how increasing knowledge of YAP/TAZ signaling might influence the trajectory of future progress in regenerative medicine.